Pluriuniversos: poesia popular, movência e distinção - Cobra, Cristiane Moreira (2016)
The object of study of this research is the popular Brazilian poetry; it aims at understanding the processes of mobility and distinction through the analysis of the personal history and work of two authors: Moreira de Acopiara e Ditão Virgílio, who perform in different contexts. What justifies this research is the comprehension of forms of creation and recreation of popular poetry found by these poets, besides the comprehension of spaces of legitimacy and acknowlegment in which their practices develop, considering the hypothesis that diverse contexts result in variations in the elements of popular Brazilian poetry. The methodoly involved etnography, interviews, field observation, analysis of the context and their personal history; the theoretical contribution was based on Pierre Bordieu. According to the research, Ditão Virgílio and Moreira de Acopiara introduced variations in the habitus constituted by institutions such as IPHAN and ABLC, under new conditions groups such as SOSACI, UCRAN and MAUDITOS arise. With this research I defend the thesis that in the field of popular poetry, segment of the field of literature, pluriuniverses, which update the tradition, are constituted and the tradition is related to the social, economical and cultural reality around the poets, generating different ways of production and reproduction of popular poetry